2012
DOI: 10.1080/09640568.2011.636578
|View full text |Cite
|
Sign up to set email alerts
|

Ecological sustainability – a customer requirement? Evidence from the automotive industry

Abstract: There are several motives for the adoption of 'green' or sustainable materials for car interiors, for example, the shortage of fossil resources and the resulting oilprice increase, new legal requirements (regulations and laws) which penalise environmental pollution and the changing behaviour patterns of consumers. The latter was the subject of an empirical study involving 106 potential car buyers, who were asked about their attitude to sustainable materials in a car interior. Furthermore, consumers' willingnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 44 publications
0
18
0
1
Order By: Relevance
“…The introduction of hybrid cars has received a great deal of attention from environmentally conscientious consumers, for whom the cars' "green" attributes can be quite attractive. It has been said that consumers' high environmental concerns have become an important factor in green product purchase decisions (Hetterich, Bonnemeier, Pritzke, & Georgiadis, 2012;Schlegelmilch, Bohlen, & Diamantopoulos, 1996;Singh, Vrontis, & Thrassou, 2011). In addition, hybrid car drivers are older than average drivers, and they form the largest demographic segment of this product category, including adults older than age 50 years, in general (Berman, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of hybrid cars has received a great deal of attention from environmentally conscientious consumers, for whom the cars' "green" attributes can be quite attractive. It has been said that consumers' high environmental concerns have become an important factor in green product purchase decisions (Hetterich, Bonnemeier, Pritzke, & Georgiadis, 2012;Schlegelmilch, Bohlen, & Diamantopoulos, 1996;Singh, Vrontis, & Thrassou, 2011). In addition, hybrid car drivers are older than average drivers, and they form the largest demographic segment of this product category, including adults older than age 50 years, in general (Berman, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…They pointed out that AHSS were not known by the general steel user and was therefore not used as widely as expected. Hetterich and colleagues () made the same conclusions when they described that the engineers’ minds had to be directed toward sustainability and that information about the value chain needed to be available in order to consider sustainability in the early process of product development. Also, Wong and colleagues concluded that communication was essential if the consumers were to be made aware of the products’ environ­mental benefits (Wong et al ).…”
Section: Discussionmentioning
confidence: 88%
“…Hetterich et al consider the specific attitude of motorists towards sustainable materials in the interior sector. The focus here is on the willingness of customers to actually pay more for renewable raw materials (Hetterich, Bonnemeier, Pritzke, & Georgiadis, 2012).…”
Section: Sustainability In the Automotive Industrymentioning
confidence: 99%
“…Some others analyse the potential of sustainability as a customer requirement, but misses the focus on automotive interior (e.g. Biju, Shalij, & Prabhushankar, 2015;Hetterich et al, 2012;Moisescu, 2018;Panuju, Ambarwati, & Susila, 2020). The article attempts to close this gap.…”
Section: Sustainability In the Automotive Industrymentioning
confidence: 99%